2018
DOI: 10.1021/acsanm.8b00095
|View full text |Cite
|
Sign up to set email alerts
|

Direct Formation of 2D-MnOx under Conditions of Water Oxidation Catalysis

Abstract: We describe the synthesis and characterization of a novel 2D-MnO x material using a combination of HR-TEM, XAS, XRD, and reactivity measurements. The ease with which the 2D material can be made and the conditions under which it can be made implies that water oxidation catalysts previously described as "birnessite-like" (3D) may be better thought of as 2D materials with very limited layer stacking. The distinction between the materials as being "birnessite-like" and "2D" is important because it impacts on our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…Materials prepared at room temperature and 110 °C were analyzed using a combination of X-ray diffraction (XRD), X-ray absorption spectroscopy (XAS), and transmission electron microscopy (TEM). The results indicated that they were structurally similar to birnessite but 2D-like or very highly c-disordered as described further below . A sample of 2D-MnO x (RT) was then heated for 24 h at 500 °C and found to be hollandite by XRD, XAS, and TEM.…”
Section: Experimental Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…Materials prepared at room temperature and 110 °C were analyzed using a combination of X-ray diffraction (XRD), X-ray absorption spectroscopy (XAS), and transmission electron microscopy (TEM). The results indicated that they were structurally similar to birnessite but 2D-like or very highly c-disordered as described further below . A sample of 2D-MnO x (RT) was then heated for 24 h at 500 °C and found to be hollandite by XRD, XAS, and TEM.…”
Section: Experimental Methodsmentioning
confidence: 72%
“…The chemical formula of the newly synthesized materials was characterized by a combination of ion chromatography, atomic emission spectroscopy (AES), titration, weight changes upon heating to 110 °C, and analysis of the XRD data (see ref ). Heating 2D-MnO x (RT) past 300 °C forces the material to undergo a transition to hollandite with sodium in the tunnel, and further heating to 800 °C causes a transition to Mn 2 O 3 .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Mn and Co at the catalytic surfaces likely adopt higher oxidation states during the OER, those cannot be detected by ex situ analysis due to their very high oxidative reactivity and immediate conversion into states that are thermodynamically favourable under ambient environment. [63][64][65] X-ray diffractograms of [Co+Sb]Oy and [Mn+Sb]Oy exhibited a set of peaks typical of a tetragonal trirutile phase with major 110, 013 and 123 reflections at ca 27, 35 and 53°, respectively (Figure 3a-b).…”
Section: Catalystmentioning
confidence: 99%
“…In other words, it is more likely to transform into an active intermediate with exact lattice orientation toward OER (Figure 9). [131,132,133,134] Therefore, the energy needed to convert the pristine material to the active intermediate phase decreases in the chaotic structure, leading to the overall energy-saving for OER. [131,132,133,134] In brief, the twisted structure from the foreign element invasion would not only lower the energy barrier (optimal MÀ O binding) during OER but also lift the energy state of the material itself, accelerating the formation of active intermediate with less needed energy input.…”
Section: Regulation Effect In Multi-metallic Oer Catalystsmentioning
confidence: 99%